The shape operator of the bezier surfaces in minkowski-3 space - Samancı, Hatice Kuşak; Çelik, Serkan; İncesu, Muhsin (Editura Bibliotheca-Bibliotheca Publ House, 2020)
Bezier surfaces are commonly used in Computer-Aided Geometric Design since it enables in geometric modeling of the objects. In this study, the shape operator of the timelike and spacelike surfaces has been analyzed in Minkowski-3 space. Then, the obtained results were applied to a numeric example.
Keywords: Minkowski space; Bezier surface; Shape operator; Timelike and spacelike surface